2018
DOI: 10.1007/s00198-017-4349-9
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of wrist fractures in older men: the Osteoporotic Fractures in Men (MrOS) study

Abstract: Among these older, community-dwelling men, we confirmed that fracture history is a strong predictor of wrist fractures in men. Medications such as SSRIs and corticosteroids also play a role in wrist fracture risk. We identified novel risk factors including kidney function and the inability to perform the grip strength test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(45 reference statements)
3
16
0
Order By: Relevance
“…The prevalence of fragility fractures is 20.5% in women ≥65 years old in the United States (US), [ 3 ] and the annual incidence of distal radius fracture for men aged ≥65 is approximately 160 per 100,000 persons in the US. [ 4 ] In Korea, the annual incidence of distal radius fractures is 246 to 278 per 100,000 persons [ 5 ] and of hip fractures is approximately 1500 in women and 5000 in men. [ 6 ] The incidence of spine fracture in Korea is estimated to be 526 to 544 per 100,000 persons in men and 1.58 to 1.60 per 100,000 persons in women; these values are higher than the worldwide incidence, which ranged from 48 to 1083 per 100,000 persons.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of fragility fractures is 20.5% in women ≥65 years old in the United States (US), [ 3 ] and the annual incidence of distal radius fracture for men aged ≥65 is approximately 160 per 100,000 persons in the US. [ 4 ] In Korea, the annual incidence of distal radius fractures is 246 to 278 per 100,000 persons [ 5 ] and of hip fractures is approximately 1500 in women and 5000 in men. [ 6 ] The incidence of spine fracture in Korea is estimated to be 526 to 544 per 100,000 persons in men and 1.58 to 1.60 per 100,000 persons in women; these values are higher than the worldwide incidence, which ranged from 48 to 1083 per 100,000 persons.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the incidence of the rst wrist fracture after the age of 50 was higher in women than in men, which was supported by the Oslo Health Study [22]. Women ages above 50 are usually in or about to enter their menopause, who are at higher risk of osteoporosis that may lead to brittle fractures [6,13,[26][27][28].…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, it is high time that we design more studies to assess the prevalence, characteristics and associated risk factors of wrist fracture, contributing to their prevention and treatment measures. However, epidemiological studies on that incidence of wrist fractures were limited [5,13]. There has not been reports on the prevalence of wrist fractures yet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to trauma, bone healing problems are usually associated with several factors, such as age, sex and infection, as demonstrated by diagnoses, such as osteopenia, osteoporosis and severe dental problems related to tooth loss [12]. For instance, osteoporosis has been recognized as one of the most important disease afflicting the global population alongside hypertension and diabetes mellitus [33], whereas its economic impact is similar to the cost of other major diseases, such as strokes, breast cancer or myocardial infarction. It is characterized by an imbalance in the bone remodeling process that leads to a progressive loss in bone mass and, subsequently, an increase in the fracture risk [34].…”
Section: Bone Fracture and Diseasesmentioning
confidence: 99%